The erotics of materialism : Lucretius and early modern poetics - Hock, Jessie (University of Pennsylvania Press, 2021)
Jessie Hock maps the intersection of poetry and natural philosophy in the early modern reception of Lucretius and his De rerum natura. Focusing on Pierre de Ronsard, Remy Belleau, John Donne, Lucy Hutchinson, and Margaret Cavendish, she demonstrates how these poets read De rerum natura as a treatise on the poetic imagination.